Kite String or Manja Cut Injury: A New Culprit - Patil, Surendrakumar B.; Gupta, Neha; Gandhi, Anshoo; Bhasin, Mayank; Rakhonde, Prabhakar; Machhale, Sushil (Indian Journal of Plastic Surgery, 2024)
Background Kite string injuries (manja cut injuries), particularly those caused by Chinese manja, are new culprit of emergencies especially in the month of January in Maharashtra region. These injuries commonly affect the neck, face, hands, and legs, especially among individuals traveling on two wheelers. The visibility challenge, where the kite's thread is difficult to see, further exacerbates the risk.Materials and Methods We have studied 10 cases of manja cut injuries presented to a tertiary care center in Nagpur during the last 2 years.Result A total of 10 patients reported kite string-related injuries to our department over a period of 2 years. All patients were male. The majority of patients presented in the younger age group with the mean age of presentation was 25 years. Majority of the patients had injuries in zone 2 of the hand.Conclusion Kite flying is a traditional festival celebrated in the month of January in Gujarat and Maharashtra for years. However, the introduction of Chinese or nylon manja has led to serious injuries and fate, affecting not only kite flyers but also bystanders, animals, and birds. This study seeks to highlight the harmful consequences of Chinese manja and deceptive appearance of manja giving false impression of simple lacerated wound which could be just a tip of the iceberg.
Keywords: kite string; Chinese manja; hand injuries